2014
DOI: 10.3390/en7010295
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Interconnect Ribs for a Cathode-Supported Solid Oxide Fuel Cell

Abstract: A comprehensive mathematical model of the performance of the cathode-supported solid oxide fuel cell (SOFC) with syngas fuel is presented. The model couples the intricate interdependency between the ionic conduction, electronic conduction, gas transport, the electrochemical reaction processes in the functional layers and on the electrode/electrolyte interfaces, methane steam reforming (MSR) and the water gas shift reaction (WGSR). The validity of the mathematical model is demonstrated by the excellent agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The effective conductivity of electrons and irons ( σ e,eff and σ ion,eff ) can be written as follows: ke/italicioneff=ke/italicion×φe/italicion0.2941+ε1+ε0.2942, …”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective conductivity of electrons and irons ( σ e,eff and σ ion,eff ) can be written as follows: ke/italicioneff=ke/italicion×φe/italicion0.2941+ε1+ε0.2942, …”
Section: Model Descriptionmentioning
confidence: 99%
“…The effective conductivity of electrons and irons (σ e,eff and σ ion,eff ) can be written as follows 68 :…”
Section: Electron and Ion Transportmentioning
confidence: 99%
“…In the past decade, low cost, clean and high efficiency energy conversation and storage devices, such as fuel cells [1], batteries [2] and super-capacitors [3], have been receiving more and more attentions. Solid oxide fuel cell (SOFC) has being recognized as a promising energy conservation device due to its efficiency [4] and capability to work with various fuels [5].…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al [4] have found through numerical simulations, that the mass transfer rate, aspect ratio and base angle have significant effects on the thermal-hydraulic parameters. Kong et al [5] and Liu et al [6] optimized the size of the gas channel for cathode-supported SOFCs and proton-conductive SOFCs with a direct interconnector. Nguyen et al [7] proposed a ribbed interconnector SOFC.…”
Section: Introductionmentioning
confidence: 99%